Wild coral oocytes are more amenable to low temperature preservation than cultured counterparts. (January 2023) - Lin, Chiahsin; Lin, Cheng-Chia; Kuo, Fu-Wen; Tsai, Sujune
Abstract: Few studies have examined the biochemical differences between cultured and wild coral after undergoing low-temperature preservation. The present study aimed to explore the differences in the biochemical characteristics of cultured and wild coral cells and oocytes ( Echinopora gemmacea and Oxypora lacera ) in cryopreservation conditions. Wild and cultured coral cells were extracted and subjected to freezing experiments involving multiple types and concentrations of cryoprotectant, and the oocytes from the cultured and wild corals were subjected to chilling experiments. Cultured and wild coral cells exhibited no significant differences in viability or cell density after cryopreservation, whereas the oocytes from the cultured corals E. gemmacea and O. lacera exhibited lower chilling tolerance compared with their wild counterparts. Significant differences were observed between the oocytes from the cultured and wild corals after low-temperature preservation, particularly in their metabolic activity and vital status, which could be possibly attributed to food consumption and environmental factors. The study provides a foundation for research promoting the technological development of artificial coral propagation and cryopreservation. Highlights: This study clarified the biochemical differences between cultured and wild corals and provided a foundation for future research on the technological development of artificial coral propagation and cryopreservation. Significant differences were observed between the oocytes from the cultured and wild corals, particularly in their metabolic activity and vital status. The freezing procedures described herein can be applied to both wild and cultured coral cells from different sites. However, the low-temperature preservation of coral oocytes would require a specific protocol based on the location where the samples are collected.